Penerapan Metode VIKOR dan WASPAS Dalam Pemilihan Handphone Bekas - Agung Triayudi (Forum Kerjasama Pendidikan Tinggi, 2022)
Mobile is a sophisticated telecommunication tool to be able to interact with fellow human beings where the communication does not look at near or long distances between people who use the cellphone in communicating well. Mobile phones also have very high capabilities, which can be similar to computers, but mobile phones can be taken anywhere because they have a very minimal size and weight compared to computers. For Mobile Users, it seems to be a need for the whole community that has been widely used by all groups ranging from children, teenagers to the elderly. There are new cellphones and there are also used ones, many prefer to buy used cellphones because besides the prices are much cheaper, even the quality is still good. Therefore, a decision support system is needed to make it easier for used cellphone enthusiasts to get cellphones with good quality and specifications. The methods used are VIKOR and WASPAS methods. The selection of used cellphones is carried out based on predetermined criteria. The results of the application of the VIKOR method with the best alternative are on A3 of 0.793 while based on the WASPAS method the best alternative is on A4 with a reference value of 0.886